Study on Seawater Intrusion Detection and Investigation in the Muar River Basin. - Shangkari Sivaraju; Mohd Shamian Zainal (Progress in Engineering Application and Technology, 2026)
Seawater intrusion is detrimental for agricultural activities, water supply, and the health of river ecosystems, such as that affecting Malaysia’s Muar River. This paper looks at an affordable, IoT system made to spot seawater intrusion as it happens.The system has a salinity sensor, an ESP32 Wi-Fi chip, and GPS for finding locations. It watches salinity and location, sending info to a web platform. The Blynk app shows the info and sends out alerts.Observations from the river mouth show salinity is reduced upstream, supporting the idea that seawater intrusion happens when the river’s discharge decreases. This system allows fast data collection and cheap early warnings, which helps with tracking the environment and handling water resources. Later studies might watch water quality and study long-term trends in the data.